Research on wear resistance of polymeric composite materials based on microparticles from tyre recyclation process - Müller, Miroslav; Rudawska, Anna; Tichý, Martin; Kolář, Viktor; Hromasová, Monika (Manufacturing Technology Journal, 2020)
A huge amount of waste comes into being from tyres which cannot already be used for their purpose. There are many ways how to utilize this waste but material recyclation is a priority. Waste tyre rubbers can be processed into a form of granulate which can be used into polymeric composite materials. This research deals with possibili-ties of tyre waste composite material utilization in areas distinguished for wear. The aim of the research was an assessment of a usage possibility of rubber powder (RP) coming into being from tyre recyclation process as a filler into a thermosetting matrix from firm Havel Composite applied into composite boards made by a vacuum infu-sion. The research focused on an evaluation of wear by friction against loosely fixed abrasive particles according to GOST 23.208-79, hardness and interaction of the matrix and the reinforcement by means of SEM analysis of the polymeric composite materials reinforced with waste microparticles arisen from tyre recyclation process. Research results proved a positive influence of the filler on the improvement of the wear resistance depending on the size of active rubber powder.
Keywords: Hardness; Mass Loss; Wear Track; Loosely Fixed Abrasive Particles; SEM